Life calendaring as a qualitative strategy to examine human security among queer emerging adult men: a pilot study - Cleofas, Jerome Visperas (Frontiers in Sociology, 2024)
Emerging adulthood has been characterized as a developmental period of insecurities and instabilities, especially among sexual minorities (i.e., queer people). This brief report proposes the utility of life calendaring as a tool to examine how queer emerging adults make sense of their security. First, this paper reviews the basic principles of human security as an approach to human development among emerging adults and explains how sexuality influences their sense of security in their present and projected lives. Second, this report explains the methodological features of life-calendaring as a qualitative research strategy and describes the process of an ongoing life-calendaring-aided interview research project that examines human security among queer emerging adult men. Finally, this article presents key insights from three life calendaring exemplars to demonstrate queering human security in emerging adulthood.